Children's Perspectives on Outpatient Physician Visits: Capturing a Missing Voice in Patient-Centered Care - Jessica S. Dalley; Barbara A. Morrongiello; C. Meghan McMurtry (MDPI AG, 2021)
Actively involving children in their healthcare is a core value of patient-centered care. This is the first study to directly obtain children's detailed perspectives on positive and negative aspects of outpatient physician visits in a primary care setting (e.g., checkups) and their preferred level of participation. Individual interviews were conducted with 167 children (female n = 82, male n = 85; ages 7-10, Mage = 8.07 years, SD = 0.82). Open-ended questions were used so that children's responses were not confined to researchers' assumptions, followed by close-ended questions to meet specific objectives. Quantitative content analysis, correlations, logistic regression, and Cochran's Q were used to explore the data. Children were highly fearful of needle procedures (61%), blood draws (73%), pain (45%), and the unknown (21%). Children indicated that they liked receiving rewards (32%) and improving their health (16%). Children who were more fearful during physician visits wanted more preparatory information (ExpB = 1.05, Waldx2(1) = 9.11, p = 0.003, McFadden's R22 = 0.07) and more participation during the visit (ExpB = 1.04, Waldx2(1) = 5.88, p = 0.015, McFadden's R22 = 0.03). Our results can inform efforts to promote positive physician visit experiences for children, reduce procedural distress, and foster children's ability to take an active role in managing their health.